Enhancing Drama Script Writing Skills through an Inquiry-Brainstorming Learning Strategy among Indonesian Language Students - Nur Amalia; Rr. Sulistyawati; Windia Hadi (STAI Hubbulwathan Duri, 2025)
Drama script writing is an essential skill for students of Indonesian Language and Literature Education programs, yet many face difficulties in vocabulary mastery, diction, punctuation, and structuring coherent storylines. To address these challenges, this study examined the effectiveness of an inquiry–brainstorming learning strategy in enhancing drama script writing skills. This quantitative research employed a quasi-experimental pretest–posttest control group design. A total of 72 fourth-semester students were randomly selected from a population of 96 and divided into experimental and control groups. The experimental group received instruction using inquiry–brainstorming learning, while the control group followed conventional teaching. Data were collected through tests, questionnaires, and observations, then analyzed using descriptive statistics, normality and homogeneity tests, and independent sample t-tests. Findings showed a significant improvement in the experimental group’s drama script writing skills compared to the control group. The post-test mean score of the experimental group (M = 82.5) was higher than that of the control group (M = 76.3), with t = 9.547 and p 0.001. Students reported higher engagement, creativity, and confidence in developing scripts. The inquiry–brainstorming strategy effectively enhanced students’ drama script writing skills and fostered critical thinking, collaboration, and literacy. Future studies should explore long-term impacts and integration with digital learning platforms.